Trade Finance and Trade Flows : Panel Data Evidence From 10 Crises - Ronci, Marcio (IMF Working Papers; Working Paper ;, 2004)
This paper assesses the effect of constrained trade finance on trade flows in countries undergoing financial and balance of payments crises. Most of the countries that had a major crisis had a significant trade contraction, while trade-related finance declined sharply. However, trade may also be affected by other variables such as world demand, domestic demand, banking crises, changes in export and import prices, and real exchange rate depreciation. To estimate the effect of constrained trade finance on trade flows, we estimate import and export volume equations including explicitly trade financing as an explanatory variable in addition to the usual variables such as relative prices and income. We conclude that constrained trade finance is a factor in explaining both export and import volumes in the short-run. A fall in external trade finance explains a relatively small part of the trade loss during crises, while a fall in trade financing in connection with domestic banking crisis can lead to a substantial loss of trade.